Photocatalytic conversion of carbon dioxide to methane using RGOAu-TNTs - Khatun, Fatema (2020)
The diversity of nanostructured material synthesis and exploring the proficient physical, chemical, and optical properties in order to investigate its catalytic efficiency is one of the most researched areas nowadays. This present study emphasizes on the reduction of immense CO2 gas in the atmosphere to valuable hydrocarbon fuel with the utilization of synthesized novel nanostructured photocatalyst. Titanium dioxide (TiO2) is one of the most widespread semiconductor photocatalysts for photocatalytic applications. Despite its eminence, it has major drawbacks in terms of higher bandgap (3.2 eV) and high recombination of photogenerated charge carriers. Due to its wide bandgap, the photoexcitation occurred only in the ultraviolet (UV) region of the electromagnetic spectrum. Moreover, the UV region is only 5% in the solar spectrum whereas the visible region comprises a total of 53%. Thus, the higher charge carrier recombination, with less visible light utilization during photoexcitation of TiO2 is one of the major challenges in photocatalytic domains. For this reason, in this study, a TiO2 based nanocomposite photocatalyst with enhanced visible light efficiency was developed through the combined electrochemical anodization, electrochemical deposition, and immersed method. The visible light absorption efficiency of the photocatalysts was revealed through UV-Vis analysis due to the LSPR nature of Au nanoparticles. In addition, the bandgap energy of the photocatalyst was reduced drastically which further shows a lower e-/h+ recombination rate attained through PL analysis. The photocatalytic performance of the prepared photocatalysts for the conversion of CO2 to CH4 yield follows an ascending order of TNTs <RGO-TNTs < Au-TNTs <RGO/Au-TNTs which are 4.1% <12.46% <22.32% <33.1%. The significant result obtained by utilizing RGO/Au-TNTs photocatalyst, for the reduction of CO2 to CH4. The total CH4 yield obtained after 2 h of photocatalytic performance for the RGO/Au-TNTs is 8.07 times higher than TNTs. To conclude, Titanium dioxide nanotube incorporated with Au was successfully synthesized through a facile electrochemical deposition method as well induced simple experimental set-up. The prolonged visible light absorption efficiency improved the TNTs e-/h+ recombination rate and enhanced the photocatalytic CO2 conversion efficiency towards visible light by employing LSPR effective Au nanoparticles and highly active RGO. Therefore, this approach opens the numerous paths for the efficient visible light photocatalyst (VLP) for utilizing a huge solar spectrum to produce hydrocarbon fuels from the excessive CO2 in the atmosphere.